Developing Digital Storybooks to Enhance Primary School Students' Scientific Literacy: A Needs Analysis - Arindya Naresti, Duta; Suratmi (Jurnal Komunikasi Pendidikan, 2024)
Science literacy skills in Indonesia are still relatively low. This study aims to analyze the need to develop learning media, especially digital storybooks, to improve the science literacy of fourth-grade elementary school students. The analysis involves literature studies, field studies with teacher interviews, and evaluating learners' science literacy abilities. The results of the analysis showed variations in learners' learning styles (visual, auditory, kinesthetic) and low science literacy needs. The teacher stated that the independent curriculum is used with learning activities that have applied science literacy, but it is still limited. The science literacy ability of students was recorded to be low, with an average percentage of 43.53%. Teachers see the need for innovation through digital learning media, especially picture storybooks, to increase students' interest and understanding of science material. Based on these findings, the development of digital storybooks can be an effective solution to improve the science literacy of fourth-grade students. It is hoped that implementing this media will help strengthen science literacy skills and improve the understanding of scientific concepts in everyday life. This research contributes to the field by providing evidence-based recommendations for integrating digital storybooks into the curriculum, thereby enhancing the effectiveness of science education in primary schools.